2021
DOI: 10.3389/fvets.2021.718036
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Energy Levels Affect Carbohydrate Metabolism-Related Bacteria and Improve Meat Quality in the Longissimus Thoracis Muscle of Yak (Bos grunniens)

Abstract: The effects of different dietary energy levels on the ruminal bacterial population, selected meat quality indices, and their relationship in yak longissimus thoracis (LT) muscle were assessed in this study. A total of 15 castrated yaks were randomly assigned to three groups with low- (NEg: 5.5 MJ/Kg, LE), medium- (NEg: 6.2 MJ/Kg, ME), and high- (NEg: 6.9 MJ/Kg, HE) dietary energy levels and occurred in the cold season (March to May). All yaks from each treatment group were humanely slaughtered and sampled on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…In the previous research, we discovered that indoor feeding increased the content of fat in sheep's LL by regulating the lipolysis in the adipocyte pathways of muscles ( 10 ). Moreover, previous reports show that the increased carbohydrate metabolism could generate more energy and substrate for the host for the synthesis of fat in muscles ( 38 , 39 ). In this study, we found a strong correlation between the fat content and the metabolism of lipids (ether lipid, glycerolipid, and glycerophospholipid) and carbohydrates (carbohydrate digestion and absorption, sucrose and starch, and galactose).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous research, we discovered that indoor feeding increased the content of fat in sheep's LL by regulating the lipolysis in the adipocyte pathways of muscles ( 10 ). Moreover, previous reports show that the increased carbohydrate metabolism could generate more energy and substrate for the host for the synthesis of fat in muscles ( 38 , 39 ). In this study, we found a strong correlation between the fat content and the metabolism of lipids (ether lipid, glycerolipid, and glycerophospholipid) and carbohydrates (carbohydrate digestion and absorption, sucrose and starch, and galactose).…”
Section: Discussionmentioning
confidence: 99%
“…This result eventually produced the difference in metabolic levels in the muscle due to a direct correlation amid the abundance of four species at the genus level ( Quinella, Ruminococcus 2, Succinivibrionaceae UCG-001, and (Eubacterium) coprostanoligenes ) and the content of the products of carbohydrate metabolism (stachyose, isomaltose, D-lactose, and maltotrios) in the LL. The high energy supply promoted the rapid proliferation of these bacteria, which in turn degrade carbohydrates ( 38 ). This process provides substrates and energy to fat synthesis and VOCs formation in the LL and thus, generates better mouthfeel, nutrition, and flavor of Black Tibetan sheep mutton.…”
Section: Discussionmentioning
confidence: 99%
“…As such, it was a better choice for producing healthy mutton products (Wang et al, 2021). Furthermore, Du et al (2021) found that a high-energy diet could enhance yak's muscle quality, including fat content and shear force of the LL. This was achieved through an increase in amylolytic bacteria and their fermentation products which were required for fatty acid synthesis (Du et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Du et al (2021) found that a high-energy diet could enhance yak's muscle quality, including fat content and shear force of the LL. This was achieved through an increase in amylolytic bacteria and their fermentation products which were required for fatty acid synthesis (Du et al, 2021). Most importantly though, the current authors previously reported that a high-energy diet could affect Black Tibetan sheep's muscle metabolism by altering the composition of rumen microbiota, with this change improving meat quality and flavor (Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies observed that dietary N utilization was improved in beef cattle as a result of the supplementation with rumen-protected methionine (RPM) [ 13 , 14 ]. Furthermore, Liu et al reported [ 15 ] that supplementation with RPL and RPM could affect rumen bacterial communities, which was positively associated with improved meat quality in yaks [ 16 ]. Cao et al [ 17 ] demonstrated that the addition of RPL and RPM to the diet also had a positive effect on growth performance of yak calves.…”
Section: Introductionmentioning
confidence: 99%